Neuromuscular NMDA Receptors Modulate Developmental Synapse Elimination - Personius, Kirkwood E. (J Neurosci, 2016)
At birth, each mammalian skeletal muscle fiber is innervated by multiple motor neurons, but in a few weeks, all but one of those axons retracts (Redfern, 1970) and differential activity between inputs controls this phenomenon (Personius and Balice-Gordon, 2001; Sanes and Lichtman, 2001; Personius et al., 2007; Favero et al., 2012). Acetylcholine, the primary neuromuscular transmitter, has long been presumed to mediate this activity-dependent process (O'Brien et al., 1978), but glutamatergic transmission also occurs at the neuromuscular junction (Berger et al., 1995; Grozdanovic and Gossrau, 1998; Mays et al., 2009). To test the role of neuromuscular NMDA receptors, we assessed their contribution to muscle calcium fluxes in mice and tested whether they influence removal of excess innervation at the end plate. Developmental synapse pruning was slowed by reduction of NMDA receptor activation or expression and by reduction of glutamate production. Conversely, pruning is accelerated by application of exogenous NMDA. We also found that NMDA induced increased muscle calcium only during the first 2 postnatal weeks. Therefore, neuromuscular NMDA receptors play previously unsuspected roles in neuromuscular activity and synaptic pruning during development. SIGNIFICANCE STATEMENT In normal adult muscle, each muscle fiber is innervated by a single axon, but at birth, fibers are multiply innervated. Elimination of excess connections requires neural activity; because the neuromuscular junction (NMJ) is a cholinergic synapse, acetylcholine has been assumed to be the critical mediator of activity. However, glutamate receptors are also expressed at the NMJ. We found that axon removal in mice is slowed by pharmacological and molecular manipulations that decrease signaling through neuromuscular NMDA receptors, whereas application of exogenous NMDA at the NMJ accelerates synapse elimination and increases muscle calcium levels during the first 2 postnatal weeks. Therefore, neuromuscular NMDA receptors play previously unsuspected roles in neuromuscular activity and elimination of excess synaptic input during development.